2022
DOI: 10.1155/2022/8296212
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Extraction Methods on Quality Characteristics of Rapeseed and Flaxseed Oils

Abstract: This study reports the effect of roasted pretreatment combined with screw press, hydraulic press, and Soxhlet extraction methods on various quality indexes of rapeseed and flaxseed oils, including the oil yield, sensory indexes (color, smell, clarity, viscosity, and colligation score), physicochemical properties (acid value, peroxide value, saponification value, moisture and volatiles), major components (fatty acid composition and triglyceride composition), and minor components (volatile compounds, total pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
0
0
Order By: Relevance
“…Principal component analysis has been increasingly used in the screening of crop germplasm resources [37][38][39][40][41]. This method was suitable for large sample sizes and index sizes in screening exercises.…”
Section: Discussionmentioning
confidence: 99%
“…Principal component analysis has been increasingly used in the screening of crop germplasm resources [37][38][39][40][41]. This method was suitable for large sample sizes and index sizes in screening exercises.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is more susceptible to oxidation, which leads to a decrease in the shelf life of the oil, which requires the addition of antioxidants [11]. Flaxseed is one of the most important plant sources with high percentage oil that had high percentage of omega-3 fatty acids, which are nutritionally important for lowering cholesterol and triglyceride [12,13] found that adding Moringa seed oil to sunflower oil at a rate of (20%) reduced the formation of toxic compounds during deep frying for a long time, while providing nutritional benefits to the oil. The study aimed to extend the shelf life of flaxseed oil, which is rich in essential polyunsaturated fatty acids by adding different proportions of Moringa Oleifera seed oil.…”
Section: Introductionmentioning
confidence: 99%